FUS-induced neurotoxicity in Drosophila is prevented by downregulating nucleocytoplasmic transport proteins. (24th August 2018) - Steyaert, Jolien; Scheveneels, Wendy; Vanneste, Joni; Van Damme, Philip; Robberecht, Wim; Callaerts, Patrick; Bogaert, Elke; Van Den Bosch, Ludo
Abstract: Amyotrophic lateral sclerosis (ALS) and frontotemporal dementia (FTD) are neurodegenerative diseases characterized by the progressive loss of specific groups of neurons. Due to clinical, genetic and pathological overlap, both diseases are considered as the extremes of one disease spectrum and in a number of ALS and FTD patients, fused in sarcoma (FUS) aggregates are present. Even in families with a monogenetic disease cause, a striking variability is observed in disease presentation. This suggests the presence of important modifying genes. The identification of disease-modifying genes will contribute to defining clear therapeutic targets and to understanding the pathways involved in motor neuron death. In this study, we established a novel in vivo screening platform in which new modifying genes of FUS toxicity can be identified. Expression of human FUS induced the selective apoptosis of crustacean cardioactive peptide (CCAP) neurons from the ventral nerve cord of fruit flies. No defects in the development of these neurons were observed nor were the regulatory CCAP neurons from the brain affected. We used the number of CCAP neurons from the ventral nerve cord as an in vivo read-out for FUS toxicity in neurons. Via a targeted screen, we discovered a potent modifying role of proteins involved in nucleocytoplasmic transport. Downregulation of Nucleoporin 154 and Exportin1 (XPO1) prevented FUS-induced neurotoxicity. Moreover, we show that XPO1 interacted with FUS. Silencing XPO1 significantly reduced the propensity of FUS to form inclusions upon stress. Taken together, our findings point to an important role of nucleocytoplasmic transport proteins in FUS-induced ALS/FTD.